Government Sanctioned Intelligent Homicide (GSIH): A Formidable Foe of Lasting Peace - Salerian, Alen J (European Journal of Applied Sciences, 2026)
The 20th century was a giant laboratory of man- made wars ,genocide and assassinations of thought leaders. This paper explores government sanctioned intelligent homicide (GSIH) of James Forrestall, JFK. RFK, MLK, John Lennon, Stanley Kubrick and Princess Diana that shadowed major wars and terror in the last century. The signature traits of GSIH include a sudden death of a thought leader yet the criminals would never face justice despite scientific evidence: medical evidence incompatible with official narrative, lost or falsified records ,altered crime scene evidence ,sudden suspicious deaths of key witnesses ,cover up and, numerous mechanical mishaps or human errors. A new forensic tool can accurately differentiate GSIH from ordinary crimes and may help combat GSIH a man -made menace for humanity that can be eradicated by scientific measures.